Levinas faces biblical figures - Lin, Yael (Lexington Books, 2014)
Levinas Faces Biblical Figures captures the drama of the encounter between a great philosopher and a text of primary importance. The book considers the ways in which Levinas's thoughts can open up the biblical text to requestioning, and how the biblical text can inform our reading of Levinas